The papacy, the Jews, and the Holocaust - Coppa, Frank J. (Catholic University of America Press, 2006)
"The papacy has long played a crucial role in western civilization. To many, its history and theology have seemed steeped in hostility toward the Jews. In the post-World War II era, the initial focus was on Pope Pius XII's stance during the Holocaust; it soon expanded, however, to the broader question of the papacy and the Jews. The present work transcends the thicket of controversy and provides a historical account of the relationship between the papacy and the Jews in the modern age, and the interaction between clerical anti-Judaism and secular anti-Semitism. In light of the polemical debate this subject has aroused during the past half century, this is no small task. In this work, author and historian Frank J. Coppa once again proves a capable guide to exploring the issues." "This work not only examines Rome's reaction during the fascist period but delves into the broader historical development and the impact of theological anti-Judaism. Coppa contends that developments are seldom, if ever, driven by a single force but flow from a multiplicity of factors. While some considerations are more important that others, their significance is to be determined by historical inquiry rather than imposed by preconception. He untangles these developments in this masterly work."--BOOK JACKET.